2015
DOI: 10.1155/2015/235720
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Safe Technique for CT Guided Lung Nodule Marking prior to Video Assisted Thoracoscopic Surgical Resection Revisited

Abstract: Aim. We describe our experience of a simple, safe, and reproducible technique for lung nodule marking prethoracoscopic metastasectomy. Thoracoscopic lung nodule resection reduces patient discomfort, complications, higher level of care, hospital stay, and cost; however, small deeply placed lung nodules are difficult to locate and resect thoracoscopically. Materials and Methods. We describe and review the success of our novel technique, where nodules are identified on a low dose CT and marked with methylene blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Several techniques have been developed to aid in the identification of pulmonary nodules, including digital palpation (11), the preoperative hookwire technique (4,5,12,13), preoperative microcoil placement (14,15), preoperative dye localization (16)(17)(18)(19)(20)(21)(22)(23)(24), fluoroscopy with contrast medium (25), intraoperative ultrasonography (26), preoperative agar marking (27), the endofinger device for tactile localization (28), radio-guidance (29), or a combination of these methods. Recently, preoperative bronchoscopic lung marking guided by virtual bronchoscopy (virtual-assisted lung mapping) has also been developed (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been developed to aid in the identification of pulmonary nodules, including digital palpation (11), the preoperative hookwire technique (4,5,12,13), preoperative microcoil placement (14,15), preoperative dye localization (16)(17)(18)(19)(20)(21)(22)(23)(24), fluoroscopy with contrast medium (25), intraoperative ultrasonography (26), preoperative agar marking (27), the endofinger device for tactile localization (28), radio-guidance (29), or a combination of these methods. Recently, preoperative bronchoscopic lung marking guided by virtual bronchoscopy (virtual-assisted lung mapping) has also been developed (30).…”
Section: Discussionmentioning
confidence: 99%
“…The indication for marking was peripheral pulmonary nodules 20 mm or less in diameter. The nodules were marked with various methods including hookwire, lipiodol and dye marking 10 . On the other hand, marking is rarely used in urological surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For dye localization, the rates of successful targeting during the localization procedure and successful localization in the operative field were 100% and 93.3-100%, respectively (Table 2) (51,52). In a study of 30 small metastatic nodules marked with methylene blue, Stephenson et al (51) reported that 93.3% of the marked nodules could be detected in the operative field and thoracoscopic resection was possible in 90% of the nodules. The major disadvantage of dye localization is rapid diffusion of dye into the surrounding lung parenchyma.…”
Section: Intraoperative Thoracoscopic Viewmentioning
confidence: 99%